2022
DOI: 10.3389/fpubh.2021.708199
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Motivations for Adopting Omnichannel Retailing: A Safety-Driven Perspective in the Context of COVID-19

Abstract: This study aims to understand the influence of COVID-19 on consumers' fears and self-protection motivations. Furthermore, the study seeks to understand the effects of these fears and motivations on consumers' intentions to use omnichannel retailing. A modified theoretical model is proposed by integrating protection motivation theory (PMT) and extending the extended parallel process model (E-EPPM). A total of 398 valid questionnaires are collected and used for further structural equation modeling analysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 121 publications
2
9
0
Order By: Relevance
“…The study anticipated that anxiety has a significant relationship with fear, risk and protection motivation (H3a-3C) except H3a. The result corroborates with the past result of Taylor ( 2019 ) and Liu et al ( 2022 ). However, more study is needed to fully comprehend the relationship between perceived severity and anxiety in the context of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The study anticipated that anxiety has a significant relationship with fear, risk and protection motivation (H3a-3C) except H3a. The result corroborates with the past result of Taylor ( 2019 ) and Liu et al ( 2022 ). However, more study is needed to fully comprehend the relationship between perceived severity and anxiety in the context of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…This study confirmed that risk, protection motivation, and fear have a positive and significant relationship with the desire to stay a shorter time at the shopping mall. These results endorsed the past study (Budd et al, 2021 ; Liu et al, 2021 ; Shah Alam et al, 2022a ; Zhang et al, 2021 ). There are some government agencies in Malaysia informing citizens of Malaysia not to visit crowded places, to stay at home, and to keep a 1-m distance from others.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations